Acute Renal Injury in Cardiac Surgery Patients - S. I. Rey; G. A. Berdnikov; L. N. Zimina; N. V. Rubtsov; M. K. Mazanov; D. A. Kosolapov; V. V. Sokolov (Неотложная медицинская помощь)
Background. Acute kidney injury following cardiac surgery remains a common and serious complication.Aim of study. To identify risk factors for the development and morphological features of acute renal injury, to assess the use of renal replacement therapy in patients after cardiac surgery.Material and methods. The study involved 66 patients who were treated in the Department of Cardiac Resuscitation of the N.V. Sklifosovsky Research Institute for Emergency Medicine from 2009 to 2018. Of these, 45 men (68.2%) and 21 women (31.8%). The mean age of the patients was 56.3±13.2 years. Clinical and anatomical analysis of material from 19 deceased patients was carried out. Depending on the use of methods of renal replacement therapy, patients were divided into two groups: Group 1 included 23 patients with acute renal injury requiring the use of renal replacement therapy; Group 2 included 43 patients where methods of renal replacement therapy were not used.Results. Hospital mortality in Group 1 was lower (34.8 and 41.9%, respectively), however, the differences were statistically insignificant (p=0.372). To identify the factors in the development of acute renal damage, a stepwise regression analysis was performed by constructing a regression model of Cox proportional hazards. Age, history of chronic kidney disease, serum creatinine level on the first day after surgery, severity of the condition according to the APACHE-II scale, increased lactate level on day 2 of the postoperative period, decreased urine output on the first day after surgery were statistically significant.Conclusion. Risk factors for the development of ARI after cardiac surgery under cardiopulmonary bypass are advanced age, CKD in history, the severity of the patient’s condition, assessed by the APACHE-II scale, increased serum creatinine on the first day after surgery, increased lactate on day 2 of the postoperative period, a decreased diuresis on day 1 after surgery. The use of RRT in patients after surgery under the conditions of AC was accompanied by a tendency to improve treatment results: in-hospital mortality in the group of patients who underwent RRT was 34.8% versus 41.9% in the group without RRT methods. Morphological and functional features of renal failure in patients with ARI were preceding chronic renal pathological processes of different etiology, mainly affecting the glomeruli, vessels and stroma, as well as acute pathological processes aggravating ARI (dyscirculatory disorder, degenerative changes, necrosis and necrobiosis tubular epithelium).